Plasma electrolytic oxidation up to four-steps performed on niobium and Nb-Ti alloys - Pereira, Bruno Leandro; Lepienski, Carlos Maurício; Seba, Viviane; Nugent, Michael J.D.; Torres, Ricardo; Kuroda, Pedro Akira Bazaglia [UNESP]; Grandini, Carlos Roberto [UNESP]; Soares, Paulo (Elsevier, 2022)
Plasma electrolytic oxidation (PEO) of up to four steps were performed on Niobium (Nb), and binary Niobium-Titanium alloys (Nbx-Ti, x = 50%, 90 wt.%), and the resulting oxidized surfaces were compared to their respective metallic substrate. The first and third steps were carried out in the phosphorus electrolyte, whereas the second and fourth steps were oxidized in the electrolyte containing calcium ions. Coatings formed from the second step were porous, with the chemical composition containing both calcium and phosphorus elements. The PEO process decreased the elastic moduli to approximately 60 GPa and increased the surface cell viability compared to the metallic surfaces without treatment. All surfaces produced from the second step-PEO demonstrated improved characteristics for application in metallic implants. Additionally, those performed on the alloys in electrolytes containing phosphate ions (up to three steps) exhibited greater performance on cytocompatibility tests.
Keywords: Four-step PEO; Niobium-titanium alloys; Plasma electrolytic oxidation